FASHARKAN SAFETY WORKING AND WELFARE ASSURANCE EFFECT TO IMPROVE THE NAVAL WARSHIPS MAINTENANCE QUALITY IN THE SECOND FLEET COMMAND - Yoyok Nurkarya; Rudi Hartono Siregar; Rahkmad Susilo; Anton Nugroho (JOURNAL ASRO, 2022)
ABSTRACT The Navy is one of the defence forces that carry out an important task in maintaining Indonesia's maritime security. In carrying out its main tasks, the Indonesian Navy currently has a power system, namely what we know as the Integrated Fleet Weapon System (SSAT), which consists of the Indonesian Naval warship (INDONESIAN NAVAL WARSHIP), Base, Marines, and Aircraft. These components require management for routine maintenance and repair management to maintain readiness when in use. Faced with these conditions, the Indonesian Navy has a work unit, namely the Maintenance and Repair Facility (Fasharkan). Occupational Safety and Health Insurance must be conducive to all personnel and is expected to increase, which has a direct impact on work productivity. Where it is hoped that productivity can be maintained and performance improved, to support Fasharkan in completing its main task, namely carrying out elemental improvements properly, on time, and with quality. The results of the improvement directly affect the level of feasibility and user satisfaction, namely the user unit. This study uses quantitative methods using SPSS-25 tools. This research looks at the direct influence of occupational safety and health guarantees on the quality of breeding elements. Where the results of testing this hypothesis were obtained, the calculated F value is greater than the F table so that can be seen the effect of occupational safety and health guarantees on the quality of repair of the elements of Koarmada II. Where the final value of the coefficient of determination (R2) effect was 24%. Keywords: Occupational Safety and Health Assurance, Work Results